2015
DOI: 10.1038/ncomms8748
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastrong ductile and stable high-entropy alloys at small scales

Abstract: Refractory high-entropy alloys (HEAs) are a class of emerging multi-component alloys, showing superior mechanical properties at elevated temperatures and being technologically interesting. However, they are generally brittle at room temperature, fail by cracking at low compressive strains and suffer from limited formability. Here we report a strategy for the fabrication of refractory HEA thin films and small-sized pillars that consist of strongly textured, columnar and nanometre-sized grains. Such HEA pillars … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
241
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 508 publications
(245 citation statements)
references
References 45 publications
(68 reference statements)
3
241
0
1
Order By: Relevance
“…[41,[45][46][47] Furthermore, scaling down a material structure down to the nanoscale can cause them to exhibit different behaviors, as compared to their bulk counterparts, in which they become stronger as their size is reduced according to the Hall-Petch relationship. [23,48,49] Therefore, it is hypothesized that a thin HEA film at nanoscale may greatly enhance the mechanical performance of the composite micro/nano structure. It is, therefore, recognized that the unique superior performance of our composite nanolattice can be ascribed to the thin HEA film with promising mechanical performance at nanoscale and the "size effect" of the structural geometry size.…”
Section: Hea Filmmentioning
confidence: 99%
See 3 more Smart Citations
“…[41,[45][46][47] Furthermore, scaling down a material structure down to the nanoscale can cause them to exhibit different behaviors, as compared to their bulk counterparts, in which they become stronger as their size is reduced according to the Hall-Petch relationship. [23,48,49] Therefore, it is hypothesized that a thin HEA film at nanoscale may greatly enhance the mechanical performance of the composite micro/nano structure. It is, therefore, recognized that the unique superior performance of our composite nanolattice can be ascribed to the thin HEA film with promising mechanical performance at nanoscale and the "size effect" of the structural geometry size.…”
Section: Hea Filmmentioning
confidence: 99%
“…[30,31] For example, Zou et al proved that the HEA at nanoscale exhibit extraordinarily high tensile strength and ductility compared to its bulk form. [23] Unfortunately, to date, no prior research pertaining to 3D nano/micro lattice in combination with nanoscale HEA has been reported yet. However, with the rapid advancement of sputtering techniques, HEA film fabricated at nanoscale can now be employed as the optimal coating material.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nitride coatings from HEA have received particular attention because of improved physical and mechanical characteristics. Most of HEA nitrides consist of 5, 6 or 7 elements, but they can incorporate up to 19 elements [38][39][40][41][42][43][44][45] resistance remains still largely unexplored. For the last few years several papers, devoted to the influence of Cu -, Au -, N + ion implantation on hardness, plasticity index and corrosion resistance were published [46][47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%